Influence of cultivation region on color, volatile compounds, phenolics, and antioxidant activity of Arabica coffee (Coffea arabica) Catuaí cultivar in Brazil - CABRAL, Daniel Velloso; BRICENO, Julio Cesar Colivet; CARDOSO, Claudio Fernandes; FILHO BRAZ, Roberto; SOUSA, Luciana Aparecida de; OLIVEIRA, Tatianne Ferreira de; SILVA, Flavio (Food Science and Technology, 2025)
Coffee is one of the world’s main commodities, with Brazil being the largest producer. When it meets production and sensory quality requirements, coffee can be classified as a specialty by the Brazilian Coffee Industry Association or Specialty Coffee Association, being recognized for its aroma and taste, defined by volatile and non-volatile organic compounds, as well as the benefits such as antioxidant activity, which can vary according to the cultivation region. This study evaluates the influence of different planting locations on volatiles, color, phenolics, and antioxidant activity in Arabica coffee (Catuaí cultivar) from five Brazilian regions. The coffees were roasted uniformly, analyzed by gas chromatography-mass spectrometry for volatiles, colorimeter for color, and liquid-solid extraction for phenolics (Folin-Ciocalteu) and antioxidant activity [2,2’-azinobis-(3-ethylbenzthiazolin-6-sulfonic acid), 2,2-diphenyl-1-picrylhydrazyl, and ferric reducing antioxidant power]. The data was treated using Analysis of variance and Tukey’s test, as well as boxplot, principal component analysis, and heatmap. The colors varied significantly between the regions. Twenty-seven volatiles were common to the 5 regions, with distinct sensory contributions such as pyridine and acetic acid in coffee from the Rio Paranaíba region, and 1-methylpyrrole for the other regions. For phenolic and antioxidant content, coffee from the Rio Paranaíba region had the highest values. It was possible to see a distinction between the coffees by planting location.